Chemical equilibrium modeling of phosphorus removal and recovery processes for advanced wastewater treatment - Liu, Jinna, author; Carlson, Kenneth, advisor; Sharvelle, Sybil, committee member; Qian, Yaling, committee member (Colorado State University. Libraries, 2018)
Phosphorus (P) is a fundamental element to all life. However, unmanaged phosphorus can create negative effects in the environment. Wastewater is a significant source of phosphorus and every day, thousands of wastewater treatment and recovery facilities treat billions of gallons of nutrient rich wastewater. During the treatment process, a large amount of sludge is produced and needs to be treated and disposed. The main process for sludge treatment is anaerobic digestion after which the solids are dewatered. However, the dewatered sludge liquor or centrate contains very high levels of nutrients (nitrogen and phosphorus) that needs to be removed from this water stream before being returned to the secondary treatment process. This recycle stream adds additional nutrients to the plant which affects treatment efficiencies and increases operating costs. Additionally, when the phosphorus, magnesium and ammonia are released in the digester, they combine and can create struvite, a mineral that can cause significant damage to equipment, pumps and piping. In many cases, nutrient removal technologies are added in the sludge and centrate treatment process. This study used chemical equilibrium modeling to examine phosphorus removal and recovery in the centrate from dewatered anaerobic digestion sludge. The chemical equilibrium of two P recovery technologies (CNP's AirPrex P-recovery process, Ostara's Pearl® P-recovery process) and one P removal method (precipitation with ferric) are modeled using MINTEQ to understand how the overall water quality changes and how this could impact downstream processes. AirPrex and Pearl® produced struvite, which can be used as green fertilizer, have several factors that influence the formation of product including pH, temperature and concentration of ions such as phosphorus, ammonia and magnesium. One of the important differences between the AirPrex and Pearl® technologies is that AirPrex is installed between the anaerobic digestion and dewatering processes, while Pearl® is installed after dewatering. Through the model work, AirPrex could reach 98% P removal and 70% P recovery at the optimal situation from the digested sludge. Pearl® could reach 97% P removal and 96% P recovery at the optimal situation from centrate. The P removal method with ferric chloride could reach almost 100% phosphorus removal.
Keywords: Pearl; Virsual MINTEQ; struvite; AirPrex